Oral function and cumulative long-term care costs among older Japanese adults: a prospective 6-year follow-up study of long care receipt data - Masashige Saito; Toshiyuki Ojima; Eisaku Okada; Yasuhiro Miyaguni; Kaori Kojima (BMJ Open)
Objectives This study evaluated the relationship between status of oral function and related long-term care service costs.Design This was a prospective 6-year follow-up study of previous survey data.Setting The data were obtained from the Japan Gerontological Evaluation Study conducted between 2010 and 2011.Participants The participants were functionally independent older adults in 12 municipalities across Japan.Interventions Care service benefit costs were tracked over 6 years using publicly available claims records (n=46 616) to monitor respondents’ cumulative care costs.Primary and secondary outcome measures The primary outcome variable was the cumulative cost of long-term care insurance services during the follow-up period. We adjusted for the presence or absence of oral function problems, age, sex, physical function and socioeconomic and lifestyle background at the time of the baseline survey.Results Tobit analysis revealed that, compared with those with no oral function problems, cumulative long-term care service benefit costs for those with one, two or three oral function problems were approximately US$4020, US$4775 and US$82 92, respectively, over 6 years. Compared with those with maintained oral function, there was a maximum difference of approximately US$8292 in long-term care service costs for those with oral function problems. With increase in number of oral function problems, there was a concomitant elevation in the cost of long-term care.Conclusions Oral function in older people was associated with cumulative long-term care insurance costs. The oral function of older people should be maintained to reduce future accumulated long-term care insurance costs. Compared with those with maintained oral function, there was a maximum difference of approximately US$8292 in long-term care service costs for those with oral function problems. The cost of long-term care was amplified as oral problems increased.